Resiliencia en una Familia Víctima de la Masacre de 12 Jóvenes del Barrio Punta del Este en el Distrito de Buenaventura en el Año 2005 (2021)
Family resilience raises the capacity for family reorganization after the crisis; this is where this research starts. The present study aims to analyze the resilient processes in a family victim of the massacre of 12 young people from Punta del Este in the Buenaventura District in 2005. For this, a very important postulate supported by Walsh (2004) is taken into account. , which raises the theoretical underpinnings that give truth to this research, the author raises family resilience and its subcategories, shared belief systems, organizational patterns, and communication and problem solving. A qualitative, descriptive methodology was used, with a case study design and a historical-hermeneutical approach. Likewise, a semi-structured interview was used for data collection; with which the results were obtained that allowed to state that in this study it was found that the victim family has effectively involved the resilient processes, taking into account that they have recovered, maintained functioning and balance, supporting the crisis and stress that this generates them. For this reason, the way they have faced the difficulty, grown, learned from it and improved in all these aspects based on the family stands out.